The results of Cherkassy region sportsmen – participants in the Olympic and Paraolympic games (1952–2012) - Ярославская [Yaroslavska L.], Лариса Петровна (Slobozhanskyi Herald of Science and Sport, 2012)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> ThedataaboutCherkassy Olympic participants is unified, the systamatic list of sportsmen is given, their results on the highest modern forums – the Olympic and Paraolympic games as well as the I Youth Games (1952–2012) are analized. The stability of sportsmen's participance in the Olympic games is proved. The article shows, that the largest results were shown by the Paraolympic sportsmen. The best results sportsmen show in athletics, rowing, gymnastics and shooting. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->